Miskin dalam Perspektif Tafsir Jalalain: Studi Pemahaman Guru-Guru Pondok Pesantren Modern Ar-Rasyid - Lubis, Ahmad Rizky Pratama (Yayasan Albahriah Jamiah Indonesia, 2025)
This study examines the concept of poverty in the Tafsir Jalalain and the understanding of the teachers of the Ar-Rasyid Modern Islamic Boarding School regarding its meaning and relevance in the contemporary social context. This study starts from the understanding that poverty is not only economic, but also touches on moral and spiritual dimensions. The study used a qualitative method with an interpretation study approach and in-depth interviews with five pesantren teachers as key informants. Data were analyzed using descriptive-analytical techniques by examining the text of the Tafsir Jalalain and relating it to the context of Islamic education. The results show that the teachers understand the concept of poverty in an integrative manner: not just material deficiencies, but also weaknesses in social and spiritual abilities that require collective concern from Muslims. They interpret the teachings of the Tafsir Jalalain as ethical guidelines that encourage concrete actions, such as the empowerment of students and social activities based on Qur’anic values. Thus, pesantren play an important role in actualizing the values ​​of classical interpretation in modern life. This study confirms that the Tafsir Jalalain remains relevant as a source of Islamic education that fosters social awareness, empathy, and justice. It is recommended that classical interpretation studies continue to be developed through an interdisciplinary approach and expanded into the context of community empowerment.